Novel Deposition Method of Crosslinked Polyethylene Thin Film for Low-Refractive-Index Mid-Infrared Optical Coatings - Taeyoon Jeon; Jieun Myung; Changsoon Choi; Komron Shayegan; Scott M. Lewis; Axel Scherer (Sensors, 2023)
Mid-infrared optics require optical coatings composed of high- and low-refractive-index dielectric layers for the design of optical mirrors, filters, and anti-reflection coatings. However, there are not many technologies for depositing a material with a refractive index of less than 2 and a low loss in the mid-infrared region. Here, we present a unique deposition method of crosslinked polyethylene thin film for mid-IR optical filter design. Polyethylene has a refractive index of 1.52 in the mid-infrared region and a small number of absorption peaks, so it is useful for making optical filters in the mid-infrared region. Only 1 keV of energy is required to crosslink the entire film by irradiating an electron beam while depositing polyethylene. In addition, crosslinked polyethylene thin film has high mechanical strength, so there is no cracking or peeling when used with germanium. This allows for the use of crosslinked polyethylene as a low refractive index for mid-infrared optical coating.